2013
DOI: 10.1051/0004-6361/201219058
|View full text |Cite
|
Sign up to set email alerts
|

A new extensive library of PHOENIX stellar atmospheres and synthetic spectra

Abstract: Aims. We present a new library of high-resolution synthetic spectra based on the stellar atmosphere code PHOENIX that can be used for a wide range of applications of spectral analysis and stellar parameter synthesis. Methods. The spherical mode of PHOENIX was used to create model atmospheres and to derive detailed synthetic stellar spectra from them. We present a new self-consistent way of describing micro-turbulence for our model atmospheres. Results. The synthetic spectra cover the wavelength range from 500 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,558
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,642 publications
(1,624 citation statements)
references
References 46 publications
17
1,558
1
2
Order By: Relevance
“…In the first approach we fixed the limb darkening coefficients w 1 and w 2 during the MCMC analysis to the values from the PHOENIX atmospheric model (Husser et al 2013). In the second we utilized the triangular sampling method proposed by Kipping (2013 3 ).…”
Section: Other Limb Darkening Prescriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first approach we fixed the limb darkening coefficients w 1 and w 2 during the MCMC analysis to the values from the PHOENIX atmospheric model (Husser et al 2013). In the second we utilized the triangular sampling method proposed by Kipping (2013 3 ).…”
Section: Other Limb Darkening Prescriptionsmentioning
confidence: 99%
“…We utilize PHOENIX model stellar spectra (Husser et al 2013) We employ an MCMC approach to find the best-fitting CPAT-absorber model. We conduct an MCMC optimization for each of the exoplanet atmosphere models in the grids of cloudy and hazy models described in Section 6.2.…”
Section: Cpat Model For Absorber Heterogeneitiesmentioning
confidence: 99%
“…Data from literature and the corresponding fits to a black body. The blue dots represents a PHOENIX stellar atmosphere similar to Fomalhaut (Husser et al 2013). The black dashed line is the best fit black body for all data points with T B = 8647 K. The green dashed line is the 870 µm -6600 µm data with T B = 5540 K. The Herschel data are denoted as red X's because they are not direct measurements of the star.…”
Section: Discussionmentioning
confidence: 99%
“…7 shows all of the stellar flux data from Table 3, along with two black bodies with TB = 8600 K (the photosphere) and TB = 5540 K (from millimetre data). A PHOENIX Stellar atmosphere model similar to that of Fomalhaut (Husser et al 2013) is also shown. The Herschel data from 70-500 µm are not a direct measurement of the stellar emission, but instead are the estimated stellar contribution to the unresolved central emission at each corresponding wavelength.…”
Section: What Can the Observations Tell Us About A Possible Close In mentioning
confidence: 94%
“…Subscript 1 refers to the hot subdwarf, for which the models included H, He, C, N, O, Mg, Si and Fe opacities. Subscript 2 refers to the cool companions for which models were extracted from the P spectral library (Husser et al 2013 of the systems in order to be able to use multiple telescopes in the radial velocity follow-up and obtain a high enough signal-to-noise for abundance analysis. High resolution optical spectra have been obtained with the VLT-UVES spectrograph on a time-span comparable to the long orbital period (Chen et al 2013 predict 400 < P orb < 1600 d) of these binaries.…”
Section: Pb 3877 -A Hypervelocity Sdb Binarymentioning
confidence: 99%